The Effect of Establishing Location, Physical Evidence, E-Wom on Customer Loyalty through Customer Satisfaction as an Intervening Variable (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
AbstractThis study aims to analyze the effect of location, physical evidence, and electronic word of mouth (e- WOM) on customer loyalty with customer satisfaction as an intervening on coffee shop customers in Semarang City. This study uses a quantitative approach with a survey method and purposive sampling technique on 100 respondents. Data processing was carried out using the SEM-PLS method using SmartPLS 4.0 software. The results showed that location and e-WOM did not have a direct effect on customer loyalty, while physical evidence and customer satisfaction had a positive and significant effect. In addition, location, physical evidence, and e-WOM were proven to have a positive effect on customer satisfaction. Other findings showed that customer satisfaction was able to mediate the relationship between the three independent variables on customer loyalty. This study confirms the importance of the role of customer satisfaction as a key factor in shaping loyalty, and shows that elements of physical experience and perception of digital information have a significant effect on overall customer perception.Keywords: Location, Physical Evidence, E-WOM, Customer Loyalty, Customer Satisfaction
Keywords: Customer Satisfaction; customer loyalty; Physical Evidence; Location; E-WOM